A large atmospheric pressure nonequilibrium open space air plasma based on a rotating electrode. (3rd April 2020) - Li, Z; Liu, J; Lu, X
Abstract: An atmospheric pressure plasma with a nozzle of 2 mm × 10 mm using air as the working gas is reported based on a rotating high voltage electrode. The plasma is driven by direct current (DC) voltage and ignited when the rotating anode approaches the fixed cathode. Then it is stretched with the rotation of the anode and blown into open space by air flow. High speed photographs show that the plasma is a U-shape like discharge channel. A 100 mH inductor is used to suppress the surge current when the gap is broken down. The peak value of the surge current reduces from about 8.5 A when no inductor is used to about 0.31 A when the inductor is used. After the plasma is ignited, for the case where a 100 mH inductor is used, the average electric field stays at about 1.5 kV cm −1 during the main discharge period, and the plasma is in a glow mode discharge. After ignition, the voltage across the discharge gap increases with time with several fluctuations. High speed photographs show that the fluctuation of the voltage is related to the short-cutting phenomenon; this short-cutting phenomenon is different from the phenomenon observed in gliding arc discharge. The gas temperature of the plasma plume measured using a thermometer is lower than 60 °C except near the cathode surface (about 98 °C).